Gluteal Necrotizing Soft Tissue Infection and Hip Osteomyelitis due to Candida Glabrata. Issue 5 (May 2023) - Henry, Reynold; McGillen, Patrick; Nassiri, Nima; Asanad, Kian; Matsushima, Kazuhide; Inaba, Kenji; Clark, Damon
Background: Necrotizing soft tissue infection (NSTI) is a rapidly progressive and often fatal infection of the soft tissue. Classically, it is attributed to bacterial infection and immunocompromised patients are particularly vulnerable. However, NSTI due to fungal infection rarely does occur, including from Candida species, and can pose a diagnostic challenge for unfamiliar providers. Expedient clinical recognition, surgical debridement, fungal tissue culture, and initiation of antifungal therapy are key. Case Presentation: We report a 39-year-old obese male with long-standing history of poorly controlled diabetes who presented to a community hospital, noted to have NSTI of the sacrum, bilateral buttocks, and left hip, and was treated only with antibiotics. After transfer to an academic center, the patient underwent aggressive debridement and tissue diagnosis of Candida glabrata NSTI was made. He received broad-spectrum antibiotic and antifungal therapy for several months. Over the course of 4 months, his infection was cleared, and his large tissue defects were reconstructed with rotation flaps and the patient was discharged home. Conclusions: Fungal NSTI is a rare entity, especially when due to Candida species. It can be exceedingly difficult to diagnose and manage, as these patients may suffer higher mortality than those with NSTI due to bacteria. A high index of suspicion for the entity, rapid debridement, intraoperative tissue culture, and treatment with appropriate antifungal therapy offers the greatest chance of survival.